PELATIHAN DESIGN GRAFIS CORELDRAW X4 SEBAGAI PENUNJANG PEMBELAJARAN BAGI GURU PADA SMAN 1 SUNGAI TABUK - Mayang Sari; Auliya Rahman; Fitrah Yuridka (JURNAL PENGABDIAN AL-IKHLAS UNIVERSITAS ISLAM KALIMANTAN MUHAMMAD ARSYAD AL BANJARY, 2016)
The progress of time is always evolving, education has undergone many changes. Among them, the learning method is not only using conventional means, but also by using a more modern way, for example media-based learning with multimedia. In addition to having various advantages it attracted many students, especially school students SMA Negeri 1 Sungai Tabuk. The purpose of this study was produced medium of learning about CorelDraw X4 which presents an interactive learning model with an attractive appearance and easy to learn, can be used in the classroom and can be studied independently at home. The benefits of this research is to give students a companion study in CorelDraw X4 study material, can also be used as a learning medium grade teacher who attracted the attention and interest of student learning when teaching material CorelDraw X4 in the classroom and to improve the quality of education.Results to be achieved in the manufacture of Media Interactive learning is the process of teaching and learning in the subjects of graphic design CorelDraw X4 material more effectively and efficiently.Keywords:  Coreldraw x4, Desain Grafis, SMA Negeri 1 Sungai Tabuk